False-Positive 18F-FDG PET/CT Uptake in Unilateral Lactation. (28th November 2020) - Yip, Joshua Wei Liang; Loh, Han; Bui, Chuong; Wong, Veronica Chi Ken; Mansberg, Robert
Abstract : A 31-year-old woman (7 months postpartum and lactating) with multiple sclerotic bone lesions was referred for an 18 F-FDG PET/CT scan for characterization. The scan demonstrated unilateral diffuse intense FDG uptake corresponding to dense soft tissue in the right breast, likely related to secretory hyperplasia. On further questioning, it was made apparent that she had only been breastfeeding from the right breast. While the left breast also demonstrated dense soft tissue to a lesser degree, no significant FDG uptake was seen. The sclerotic bone lesions were not FDG avid, likely due to a separate non-FDG avid benign condition or bony metastases from a non-FDG avid primary malignancy. This was reinforced by the fact that subsequent investigations including serial bilateral breast ultrasound and percutaneous biopsy demonstrated no definite evidence of malignancy in the bilateral breasts. The histopathology findings of an open surgical biopsy of sclerotic lesions in the left posterior ilium were also nonspecific, favouring bone dysplasia with no evidence of malignancy.